Pengaruh kadar protein dan jumlah sel CSF terhadap angka kejadian malfungsi VP shunt di RS. H. Adam Malik Medan - Indra Saputra; Rr. Suzy Indharty; A. Gofar Sastrodiningrat (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Hydrocephalus is a disorder formation or absorption of fluid flow cerebrospinal. Number of cases of hydrocephalus in the world is quite high at around 0.5 -4 per 1000 live births while in Indonesia as much as 2-3 per 1000 live births. Ventriculoperitoneal shunt (VP shunt) is the main option in the treatment of hydrocephalus. One of the complications that occur in the installation of VP shunt was VP shunt malfunctions that happen as much as 25-40% especially in the first year after installation of VP shunt.Methods : The study was conducted on 169 hydrocephalus patients who performed the installation VP shunt in Haji Adam Malik Hospital Medan since January 2010 to December 2012. The data were analyzed using chi square and p values <0.05 were considered as significant.Results : In the 169 patients who performed the installation of VP shunt, 47 patients (27.8%) of them had VP shunt malfunction. Among the 47 patients who had malfunctions of VP shunt, 16 patients (40%) had shown increased of total cerebrospinal fluid protein and it had been statistically significant association between the incidence of VP shunt malfunction with cerebrospinal fluid protein levels (p = 0.049). While the examination of the number of cells in the cerebrospinal fluid of 47 patients who had VP shunt malfunctions, 14 patients (36%) had shown the increasing of number of cells in the cerebrospinal fluid and this indicates that the relationship of the incidence of VP shunt malfunction with the number of cells in the cerebrospinal fluid was not statistically significant (p =0.199).Conclusion : There is a significant correlation between cerebrospinal fluid protein levels with the incidence of VP shunt malfunction. While the number of cells in the cerebrospinal fluid showed no significant correlation with the incidence of VP shunt malfunctions.Keywords : Malfunction; VP shunt; protein; cel count; cerebrospinal fluid; Hydrocephalus